THE USE OF RCRR (READ, COVER, REMEMBER, RETELL) STRATEGY TO HELP TENTH GRADERS IN COMPREHENDING NARRATIVE READING TEXT - Regita, Anita Valeri (RETAIN, 2021)
Read, Cover, Remember, Retell (RCRR) strategy is a learning strategy with an excellent concept to teach the students to comprehend a reading text. Moreover, this study is aimed to find out the use of the Read, Cover, Remember, Retell (RCRR) strategy in teaching narrative reading text done by the teacher in the virtual classroom. This study also tried to determine the students' reading comprehension after practicing the RCRR strategy in the teaching and learning process. The base of this study was using descriptive qualitative as the research design through an observation. Furthermore, the field notes used to collect the data during the teaching and learning process using the RCRR strategy. In three meetings, the teacher implemented the RCRR strategy stages starting from reading, covering, remembering, and retelling sequentially. The field notes showed that the teacher began the learning process by doing pre-teaching activities. Then, the teacher applied read, cover, remember, and retell stages while teaching activities. Moreover, the students' narrative story retelling used to know the students' reading comprehension after the implementation, and it was analyzed by narrative story retelling rubric. This study found that the teacher applied all of those RCRR strategy stages in the teaching-learning process and can help the students comprehend narrative reading text well.